Studi Tafsir Tematik Tentang Penciptaan Manusia Dalam Tafsir Al-Munir Karya Wahbah Az-Zuhaili - Muhammad Muhyiddin Ahsan Sumarsono; Muhammad Amrulloh; Indri Astuti (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the process and purpose of human creation in the Qur’an based on Tafsir Al-Munir by Wahbah Az-Zuhaili. The focus of the study is directed at the characteristics of Az-Zuhaili’s interpretation, the stages of human creation, and the objectives of human creation, which include worship (‘ibādah), vicegerency (khalīfah), and trust (amānah). This research employs a qualitative method with a thematic (maudhu‘i) tafsir approach by analyzing Qur’anic verses related to human creation, particularly QS. Al-Mu’minun [23]: 12–16 and QS. Al-Insan [76]: 2, with Tafsir Al-Munir as the primary source. The findings indicate that Wahbah Az-Zuhaili interprets the verses of human creation in a comprehensive and moderate manner by integrating tafsir bil-ma’thūr and tafsir bil-ra’y, emphasizing the interconnection between biological, spiritual, and eschatological dimensions. The process of human creation is understood as a systematic and purposeful sequence that reflects Allah’s power and wisdom, while also affirming human accountability in worldly life. Furthermore, the purpose of human creation in Tafsir Al-Munir is formulated through the concepts of worship as total submission to Allah, vicegerency as a mandate to manage the earth responsibly, and trust as a form of moral and legal responsibility. This study concludes that the concept of human creation in Tafsir Al-Munir is not merely theological, but also carries significant moral and social implications for shaping faithful, ethical, and responsible human character.